2011
DOI: 10.5558/tfc2011-053
|View full text |Cite
|
Sign up to set email alerts
|

Predicting maximum branch diameter from crown dimensions, stand characteristics and tree species

Abstract: Forest resource inventories must include wood quality information to support the optimum use of wood fibre. The objective of this study was to develop models relating maximum live branch diameter (MBD), which affects lumber value, to tree and stand characteristics that can be measured through current and emerging remote sensing technologies. Using non-linear mixed effects models for six Canadian conifer species, as well as for three broad-leaved species, MBD was related to crown radius, tree height, crown leng… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
12
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 20 publications
7
12
1
Order By: Relevance
“…For all tree height classes, branch sections of approximately 3 cm diameter represent the largest volume in the tree canopies. This is in line with previous studies of canopy size distributions (Groot and Schneider 2011). When the volume distributions are normalized with that of the 3 cm diameter cylinder sections (Fig.…”
Section: Branch Size Distribution and Tree Heightsupporting
confidence: 76%
“…For all tree height classes, branch sections of approximately 3 cm diameter represent the largest volume in the tree canopies. This is in line with previous studies of canopy size distributions (Groot and Schneider 2011). When the volume distributions are normalized with that of the 3 cm diameter cylinder sections (Fig.…”
Section: Branch Size Distribution and Tree Heightsupporting
confidence: 76%
“…Correspondingly, the CFAR project found that MBD was strongly related to crown radius for a number of species (Groot and Schneider 2011), a result previously obtained by Garber and Maguire (2005). MBD also increased with height and decreased with stand basal area and basal area of larger trees, likely because of the effects of wind loading and competition on branch architecture (Groot and Schneider 2011, Fig.…”
Section: Progress In Predicting Mbd From Crown Characteristicsmentioning
confidence: 53%
“…Diameter at breast height Cortini et al (2011), Filipescu et al (2012 Maximum branch diameter Groot and Schneider (2011) Sapwood area distribution (longitudinal) Cruickshank et al (in review) Ring area distribution (longitudinal) Cortini et al (2013) Wood density, microfibril angle, Cortini et al (2014) Attribute variation in three dimensions is ignored when dimensionality is reduced by restricting measurements to only part of the tree. For example, measurements of wood density at the breast height part of the stem do not take into account any vertical dependence of this property and may provide a poor indication of wood density over the entire tree (Repola 2006).…”
Section: Fibre Attribute Publicationsmentioning
confidence: 99%
See 2 more Smart Citations